Regulation of phagolysosomal activity by miR-204 critically influences structure and function of retinal pigment epithelium/retina. (23rd July 2019) - Zhang, Congxiao; Miyagishima, Kiyoharu J; Dong, Lijin; Rising, Aaron; Nimmagadda, Malika; Liang, Genqing; Sharma, Ruchi; Dejene, Roba; Wang, Yuan; Abu-Asab, Mones; Qian, Haohua; Li, Yichao; et al.
Abstract: MicroRNA-204 (miR-204) is expressed in pulmonary, renal, mammary and eye tissue, and its reduction can result in multiple diseases including cancer. We first generated miR-204 −/− mice to study the impact of miR-204 loss on retinal and retinal pigment epithelium (RPE) structure and function. The RPE is fundamentally important for maintaining the health and integrity of the retinal photoreceptors. miR-204 −/− eyes evidenced areas of hyper-autofluorescence and defective photoreceptor digestion, along with increased microglia migration to the RPE. Migratory Iba1 + microglial cells were localized to the RPE apical surface where they participated in the phagocytosis of photoreceptor outer segments (POSs) and contributed to a persistent build-up of rhodopsin. These structural, molecular and cellular outcomes were accompanied by decreased light-evoked electrical responses from the retina and RPE. In parallel experiments, we suppressed miR-204 expression in primary cultures of human RPE using anti-miR-204. In vitro suppression of miR-204 in human RPE similarly showed abnormal POS clearance and altered expression of autophagy-related proteins and Rab22a, a regulator of endosome maturation. Together, these in vitro and in vivo experiments suggest that the normally high levels of miR-204 in RPE can mitigate disease onset by preventing generation of oxidative stress and inflammation originating from intracellular accumulation of undigested photoreactive POS lipids. More generally, these results implicate RPE miR-204-mediated regulation of autophagy and endolysosomal interaction as a critical determinant of normal RPE/retina structure and function.